2015
DOI: 10.1002/qre.1779
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis and Evaluation of Differential System Based on low Load Strengthening Model

Abstract: The differential is an important part of a driveline, and differential performance is related to the handling and stability performance of a vehicle. Thus, a differential with sound design structure and reasonable form and size parameters could lead to satisfactory driving performance. In this work, we analyze and evaluate the reliability of the key parts of a differential system. Firstly, each of key parts is regarded as a subsystem of a differential system, so the subsystem reliability models are obtained. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…The failure caused by wear is a fuzzy event, that is to say, wear to what extent is a fuzzy concept. On this occasion, we should adopt the fuzzy reliability design [23].…”
Section: ) Stress-strength Interference Modelmentioning
confidence: 99%
“…The failure caused by wear is a fuzzy event, that is to say, wear to what extent is a fuzzy concept. On this occasion, we should adopt the fuzzy reliability design [23].…”
Section: ) Stress-strength Interference Modelmentioning
confidence: 99%
“…1 Therefore, it is necessary to decompose it into units, which are easy to study; then the decomposed units are analyzed, and the PAPRA of the whole machine can be evaluated finally by the coupling relationship between the decomposed units. [5][6][7][8][9][10] The life cycle of electromechanical product is dynamic; the function and performance of the whole machine are realized by the function and performance of components, and the function and performance of the components are determined by the motion transfer relationship between parts. [5][6][7][8][9][10] The life cycle of electromechanical product is dynamic; the function and performance of the whole machine are realized by the function and performance of components, and the function and performance of the components are determined by the motion transfer relationship between parts.…”
Section: Introductionmentioning
confidence: 99%
“…The current decomposition methods for electromechanical product are mostly based on the structure of product or component system, such as literature [2][3][4] The smallest unit obtained by these methods is part; the decomposition results can also not reflect the characteristics of electromechanical product that 'action determines function and performance', and it is not reasonable to take them as research objects. [5][6][7][8][9][10] The life cycle of electromechanical product is dynamic; the function and performance of the whole machine are realized by the function and performance of components, and the function and performance of the components are determined by the motion transfer relationship between parts. Therefore, it can be concluded that the failure of electromechanical product's function and performance is ultimately caused by the failure of mechanical parts' motion state.…”
Section: Introductionmentioning
confidence: 99%
“…Complex mechanical products (CMPs) consist of a large number of different types of components and parts, featuring complex design, long R&D cycles, complex coupling between parts, and high manufacturing costs . At present, many studies have performed in‐depth research on the design, remanufacturing, and assembly of CMPs, which often involve the study of influential components and parts . Research on the influential parts of a CMP shows that the influential parts are the core of the product architecture and are of great importance to the reliability of a CMP.…”
Section: Introductionmentioning
confidence: 99%